The maze of language policy A study of minority languages in Aragón - Kovács Írisz (2025)
Aragón is an autonomous community located in the north-eastern part of Spain. Like manyother Spanish regions, it possesses its own linguistic identity, with Aragonese and Catalantraditionally spoken in certain areas. In recent years, the situation of Aragón's minority languageshas become the focus of significant legal and political debate. In 2023, legal reforms introducedby the coalition of the People's Party (PP) and Vox dramatically altered the region's approachto minority languages. These reforms eliminated the explicit recognition of Catalan and Aragonese as part of the region's cultural heritage, replacing them with generic labels referringto "eastern" and "Pyrenean" language varieties. This move marked a return to the policies of2013, which had significantly restricted the legal protection and cultural recognition of theCatalan and Aragonese languages. The reforms have sparked considerable social and politicalopposition. Supporters argue that the law recognises Aragón's linguistic diversity withoutimposing a rigid framework that privileges Catalan or Aragonese over other regional dialects.However, civil organisations and cultural movements accuse the government of underminingthe protection and use of minority languages, in contradiction with the commitments madeunder the Spanish Constitution and the European Charter for Regional or Minority Languages.
Keywords: Jogtudomány